Metronomic chemotherapy for metastatic breast cancer: a systematic review of the literature = Die metronomische Chemotherapie bei der Behandlung von metastasierendem Mammakarzinom : eine systematische Literaturrecherche - Banys-Paluchowski, Maggie; Schütz, Florian; Ruckhäberle, E.; Krawczyk, N.; Fehm, Tanja (Geburtshilfe und Frauenheilkunde, 2016)
Conventional chemotherapy is generally administered in high doses followed by a treatment-free period to give the body needful time to recover. This “maximum tolerated dose” approach results in high response rates. However, long periods between therapy cycles can lead to development of resistance mechanisms and consequently disease progression. One of the most interesting alternative strategies is metronomic chemotherapy. This concept relies on the continuous administration of chemotherapy at low doses and aims at targeting endothelial cells in the tumor bed as well. Recently, metronomic chemotherapy has been incorporated into the recommendations issued by the German AGO expert panel (www.ago-online.de). A systematic review of PubMed/Medline, ClinicalTrials.gov, the European Clinical Trials Database (EudraCT) and the Cochrane Database was conducted. In the present review, we discuss the current evidence on metronomic chemotherapy in metastatic breast cancer.
Gesehen am 19.08.2020